Remdesivir and Coronavirus Disease 2019 (COVID-19): Essential Questions and Answers for Pharmacists and Pharmacy Technicians - Veronin, Michael A. (J Pharm Technol, 2020)
Objective: To conduct a review of the investigational drug remdesivir and its therapeutic potential for treatment of COVID-19, in the form of a series of questions and answers. The purpose of the review is to narrow gaps in knowledge, clarify concepts, and to investigate research advancements for health care professionals. Data Sources: From June 2020 to August 2020, we conducted comprehensive searches of MEDLINE-PubMed, Scopus, and Google Scholar databases with no time limitations. Search terms were included that contained the terms “remdesivir,” “COVID-19,” “novel coronavirus” and “evidence,” “therapy,” “safety,” “effectiveness,” “efficacy,” “clinical trial.” Study Selection and Data Extraction: The sources of information include all publicly available data from previously published research reports. Reports must have at least one reference to remdesivir as a treatment modality for COVID-19 with no specified outcomes. Data Synthesis: Major research findings on the efficacy and safety of remdesivir are summarized in tabular format and presented in chronological order. Results of this review reveal remdesivir to be an effective therapy in specific clinical contexts; however, in several areas, available data are insufficient to support evidence-based guidance for remdesivir in the treatment of COVID-19. Conclusions: Clinical trials on remdesivir are ongoing, yet questions remain and further research is needed as to the selection of patients, effectiveness, and duration of treatment in the use of remdesivir for treatment of COVID-19.